The Romanian People Versus Corruption. The Paradoxical Nexus of Protest and Adaptation - Tina Olteanu (Coordinamento SIBA, 2018)
Corruption has been widely perceived as one of the main obstacles to Romania's successful transformation from socialism to democracy (and capitalism). Still, in the ensuing years after the 1989 transition, it did not directly stimulate mobilization and protest from below. However, more recently, the country has been undergoing a civic awakening. This article focuses on the interplay between the Romanian government and citizens to identify the dynamics of the growing anti-corruption protests in Romania since 2012. Four episodes of grass-roots mobilization (Austerity-2012, Rosia Montana-2013, Colectiv-2015 and OUG13/#rezist-2017) are systematically examined, taking into account the political opportunity structures and developing dynamics of contention. While these protests have been quite successful in achieving articulated demands, they have not yet transformed into sustained social movements with a wider political agenda of social change.